STUDI PENGENDALIAN REALISASI WAKTU DAN BIAYA PADA PROYEK PEMBANGUNAN THE LEGACY HOTEL TEROGONG: (Studi Kasus : Proyek Konstruksi Pembangunan The Legacy Hotel Terogong PT. Kreasi Aditama Darmalaksana) - Falih Fadhil Akbar Utomo; Muhammad Nafhan Isfahani (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
The Earned Value concept is one that is used in project management that integrates costs and time. The Earned Value concept presents three dimensions, namely the physical completion of the project which reflects the cost absorption plan, the actual costs incurred and what is obtained from the costs incurred or what is called (earned value). This study aims to obtain the calculation results of BCWP, BCWS, and ACWP. Comparison of BCWP, BCWS, and ACWP calculations. Obtain the calculation results of CV, SV, CPI, SPI, ETC, EAC, SETC, SEAC, and ECD on the construction project of The Legacy Hotel Terogong. The results of this study show that the BCWS results until the 21st week are Rp. 3,477,770,496, BCWP Rp. 3,486,573,264, ACWP Rp. 3,366,043,056. The results of the comparison of the BCWS, BCWP, and ACWP graphs are that the BCWP graph is higher than the BCWS graph, meaning that the costs incurred are higher than the planned costs, the ACWP graph is higher than the BCWP graph, meaning that until the 21st week the project is profitable. In the implementation the average SPI value is> 1, so it can be seen that the time-based project performance indicators (SPI) are in accordance with the original plan up to the 21st week. The results of this research using the Earned Value concept are very suitable for the development project of The Legacy Hotel Terogong.